ИНВАРИАНТНЫЕ СИСТЕМЫ АВТОМАТИЧЕСКОГО УПРАВЛЕНИЯ С РЕЛЕЙНЫМ УСИЛИТЕЛЕМ - Каландаров, И.И.; Буронов, Б.М.; Калханов, П.Ж. (SCIENCE and SOCIETY, 2022)
The principles of construction and calculation methods are described for invariant automatic control systems with a relay amplifier operating in the mode of self-oscillations.